2020
DOI: 10.1038/s41598-019-57106-2
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal barrier function is maintained with aging – a comprehensive study in healthy subjects and irritable bowel syndrome patients

Abstract: Animal studies have shown that intestinal barrier function is compromised with aging. We aimed to assess the effects of aging on intestinal barrier function in humans in vivo and ex vivo. In this crosssectional study, healthy subjects and subjects with irritable bowel syndrome (IBS) of older (65-75 years) and young adult age (18-40 years) were compared. In vivo gastrointestinal site-specific permeability was assessed by a multi-sugar test, taking into account potential confounders. Sigmoid biopsies were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 27 publications
1
49
0
2
Order By: Relevance
“…A recent study found that elderly IBS patients have greater disruption of small intestinal barrier compared with their younger counterparts. 110 Another study, however, found no effect of adjusting for age on permeability changes in IBS-D. 50 Furthermore, the expression of several tight junction (occludin, ZO-1 and CLDN-1) and adherens junction (JAM-1 and E-cadherin) molecules was not correlated with age in IBS patients. 49 , 85 , 87 , 90 There is an established female predominance in IBS.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that elderly IBS patients have greater disruption of small intestinal barrier compared with their younger counterparts. 110 Another study, however, found no effect of adjusting for age on permeability changes in IBS-D. 50 Furthermore, the expression of several tight junction (occludin, ZO-1 and CLDN-1) and adherens junction (JAM-1 and E-cadherin) molecules was not correlated with age in IBS patients. 49 , 85 , 87 , 90 There is an established female predominance in IBS.…”
Section: Discussionmentioning
confidence: 99%
“…Increased intestinal permeability has been reported in inflammatory bowel disease, diabetes, and more recently HF, where leakage of pancreatic enzymes into the circulation is exacerbated by gut oe- dema and hypoperfusion. 40,45,49,51 Whereas the rapid appearance of trypsin (within minutes) after a high fat diet meal 26 suggests that trypsin acutely leaks out of the small intestine, under chronic HF conditions leakage out of the intestine and/or the pancreas are possible. Ultimately, to further resolve the question about the exact source of trypsin there is a need to trace its activity during food administration of isotopically labelled trypsin and its detection in serum using mass spectrometry.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor (TNF)-α is a key regulator of intestinal inflammation and is responsible for increasing the permeability of intestinal TJs. Activation of TNF-α leads to rapid activation of the NF-𝜅B/p65 signaling pathway [ 20 , 21 ]. Therefore, p65 is considered a biomarker of the activation of inflammation-related pathways affecting intestinal barrier function.…”
Section: Discussionmentioning
confidence: 99%